2019
DOI: 10.2196/13602
|View full text |Cite
|
Sign up to set email alerts
|

The Internet Intervention Patient Adherence Scale for Guided Internet-Delivered Behavioral Interventions: Development and Psychometric Evaluation

Abstract: Background Patient adherence is defined as the extent to which a patient complies with medical or health advice. At present, there is a lack of reliable and valid measures specifically designed to measure adherence to internet-delivered behavioral interventions. Objective The objective of this study was to develop and psychometrically evaluate a novel measure of adherence to guided internet-delivered behavioral interventions. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Other secondary clinician-rated outcomes include general functioning measured with the Children’s Global Assessment Scale (CGAS) [ 40 , 41 ], and participant adherence to the internet-delivered interventions measured with the Internet Intervention Patient Adherence Scale (iiPAS) [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other secondary clinician-rated outcomes include general functioning measured with the Children’s Global Assessment Scale (CGAS) [ 40 , 41 ], and participant adherence to the internet-delivered interventions measured with the Internet Intervention Patient Adherence Scale (iiPAS) [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…While it has been suggested that increased engagement in online interventions may predict better outcomes in the prevention and treatment of depression (Christensen et al 2002;Christensen et al 2006;Van Voorhees et al 2011), the relationship between use and outcome may not be linear (Donkin et al 2013). Moreover, it is possible that our current measures of adherence (e.g., modules completed, time logged in) may not be reliable if, for example, some intervention users practice applying the concepts they have learned while not logged into the program (Lenhard et al 2019). At this point, there is no evidence to suggest that there is a threshold effect for the use of this or related interventions; in fact, participants in this and similar technology-based depression prevention programs exhibited preventive benefits using only a few modules (Gladstone et al 2018;Ip et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The clinician-rated Internet Intervention Patient Adherence Scale (iiPAS) was used in the ICBT group as a brief clinician-rated measure of adherence to internet-delivered interventions. The iiPAS has demonstrated robust psychometric properties and associations with objective measures of ICBT patient adherence ( Lenhard et al, 2019 ). The Obsessional Compulsive Inventory – Child version (OCI-CV) is a self-rated measure of OCD symptom severity.…”
Section: Methodsmentioning
confidence: 99%